Social Transformation and Ethical Challenges - Aydın, Çağdaş (IGI Global, 2025)
This study examines the critical social challenges, particularly ethical issues and social disruption, that emerged during tourism development in the South Aegean region of Turkey between 1960 and 2010. Using qualitative research methodology and document analysis, it analyzes the historical development of the tourism movement in the region and the changing roles and relationships between the main actors of tourism: locals, investors, and tourists. The study concludes that tourism's rapid and unplanned development in the South Aegean region has led to significant ethical violations and social disruption. It emphasizes the need for sustainable and ethical tourism practices that involve local people in decision-making processes, protect cultural heritage, and provide balanced benefits for the tourism industry and local communities. Implementing these practices is critical to mitigating negative impacts and ensuring the long-term sustainability of tourism in the region.